REPRESENTATION OF LGBT STRUGGLE IN THE FILM BOHEMIAN RHAPSODY - Radiyan, Wildan Bisma; Febriana, Poppy (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the representation of Freddie Mercury’s struggle to embrace and defend his LGBT identity as depicted in the film Bohemian Rhapsody, highlighting how cinema can serve as a medium for addressing issues of sexuality and identity. Method: Employing a qualitative approach, the research utilizes John Fiske’s semiotic theory of “television codes,” which operates at the levels of reality, representation, and ideology, to analyze key scenes. Data were collected through in-depth viewing of the film and systematic documentation of scenes that illustrate Mercury’s negotiation of his bisexual identity. Results: The findings indicate that the film portrays Mercury’s personal journey as both an internal and external struggle, reflecting broader societal tensions surrounding LGBT identity. Through narrative structure, character interactions, and symbolic cinematic codes, Bohemian Rhapsody presents Mercury’s challenges and resilience in asserting his identity. Novelty: This study contributes to film and cultural studies by applying semiotic analysis to demonstrate how mainstream cinema represents LGBT struggles, offering new insights into the intersection of identity, media representation, and social discourse.